1992
DOI: 10.1021/j100194a056
|View full text |Cite
|
Sign up to set email alerts
|

Structural role of water in sodium silicate glasses: results from silicon-29 and proton NMR spectroscopy

Abstract: 6405the function vRAB is small. The expansions of the two Bessel functions are KO(YRAB) = -In (vRAB)ym + In (2) ... K~(YRAB) = (vRAB)-' ...where ym is the Euler Mascharoni constant. Using these two expressions in eq 13, we obtain for the diffusion coefficientUsing the Arrhenius expression for the diffusion coefficient and for the diffusion-controlled rate coefficient and the definition of Y , given in eq 12, we arrive at kdc 217 Using the definition of T given in eq 2, we expand the rightmost expression in eq … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

24
69
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(95 citation statements)
references
References 3 publications
24
69
1
Order By: Relevance
“…Their physical and chemical properties can be better understood using structural characterizations, for example to determine whether the presence of water depolymerizes the glass network. Although this is still a subject of discussion (Zeng et al, 2000;Padro et al, 2003), these studies have extended our knowledge concerning proton sites using various NMR techniques (Kü mmerlen et al, 1992;Schaller and Sebald, 1995;Robert et al, 2001;Ai et al, 2004;Cody et al, 2005). Hydroxyl groups and molecular water are routinely observed in hydrated aluminosilicates such as albite (Kohn et al, 1989a) with 1 H chemical shifts approximately ranged from 0 to 20 ppm.…”
Section: Introductionmentioning
confidence: 99%
“…Their physical and chemical properties can be better understood using structural characterizations, for example to determine whether the presence of water depolymerizes the glass network. Although this is still a subject of discussion (Zeng et al, 2000;Padro et al, 2003), these studies have extended our knowledge concerning proton sites using various NMR techniques (Kü mmerlen et al, 1992;Schaller and Sebald, 1995;Robert et al, 2001;Ai et al, 2004;Cody et al, 2005). Hydroxyl groups and molecular water are routinely observed in hydrated aluminosilicates such as albite (Kohn et al, 1989a) with 1 H chemical shifts approximately ranged from 0 to 20 ppm.…”
Section: Introductionmentioning
confidence: 99%
“…Spectral interpretations are expected to be more straightforward for aluminum-free silicate compositions, which are thus ideal starting point for identifying and quantifying the variety of water species. Despite this advantage, there have been only limited spectroscopic studies, in particular NMR studies, on aluminum-free silicate compositions, and most of the NMR studies have been concentrated on silica and sodium silicate compositions (Farnan et al, 1987;Koller et al, 1990Koller et al, , 1995Kümmerlen et al, 1992;Schaller and Sebald, 1995;Zotov and Keppler, 1998;Robert et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…This should not be confused with non-hydrogen-bonded SiOH groups that are also sometimes referred to as "free hydroxyls" in the glass literature (e.g., Scholze, 1959a,b;Wu, 1980). 29 Si magic angle spinning (MAS) and 1 H-29 Si cross-polarization (CP) MAS NMR results on silica and sodium silicate glasses and melts (Farnan et al, 1987;Koller et al, 1990Koller et al, , 1995Kümmerlen et al, 1992;Schaller and Sebald, 1995;Zotov and Keppler, 1998;Robert et al, 2001) have revealed that the glass and melt structures become more depolymerized with water dissolution, suggesting that the formation of SiOH through the rupture of Si-O-Si linkages is a major water dissolution mechanism. The reported 1 H MAS NMR spectra for hydrous silica, and sodium-, barium-, and strontiumsilicate glasses show peaks in the range between 2.7 and 17 ppm that have been attributed to molecular H 2 O and SiOH groups (Kohn et al, 1989a;Kümmerlen et al, 1992;Schaller and Sebald, 1995;Robert et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…For example, experimental studies in binary metal oxide silicate melts may illuminate how alkali metals and alkaline earths interact with dissolved H 2 O and the extent to which H 2 O may react with bridging oxygen to form Si-OH groups in the melts and glasses (e.g., Mysen and Virgo, 1986;Kummerlen et al, 1992;Zotov et al, 1996;Zotov and Keppler, 1998). Existing data demonstrate that OH bonding involving alkalis and alkaline earths is possible, but there exist, to the knowledge of the authors, no systematic data on relationships between H 2 O solubility and solubility mechanisms, H 2 O content and the alkali/ silicon ratio of the melts (degree of melt polymerization).…”
Section: Introductionmentioning
confidence: 99%